CLINICAL AND ECONOMIC EVALUATION OF IVABRADINE USE IN STABLE ANGINA IN TERMS OF REPUBLIC OF BELARUS HEALTH CARE SYSTEM - I. N. Kozhanova; I. S. Romanova; L. N. Gavrilenko; A. V. Patseev; M. M. Sachek (Фармакоэкономика, 2015)
stable angina is a socially significant disease that requires significant financial costs to the health system and patients. In recent years the increased heart rate has been considered as a significant risk factor for poor prognosis in stable angina. The aim of the research: assessment of the economic viability of the inclusion of ivabradine in the scheme of treatment of stable angina in terms of health care system of the Republic of Belarus. Material and methods. Markov’s model of ivabradine use in patients with stable angina pectoris has been constructed on the basis of a systematic review of the literature, national surveillance data, local health services market and cardiovascular drugs market estimation. “Cost-effectiveness” and “cost-utility” analyses have been used. The target population of patients suffering from angina pectoris and in need of ivabradine prescription has been estimated with data from clinical studies and national epidemiological data. The potential effectiveness of ivabradine in the Belarusian patient population has been evaluated. Results. The size of the target patient population with stable angina for the ivabradine prescription was 17559 people. The use of ivabradine within 18 months in the target population patient with increased heart rate would allow potentially prevent 366 cases of nonfatal myocardial infarction and unstable angina, 143 cases of cardiovascular death, 391 case of revascularization. According to the results of the analysis the prescription of ivabradine in optimum dose with a minimum cost per 1 mg is the optimum pharmacoeconomic acceptability in patients with stable angina and high heart rate (70 beats per minute).